2008
DOI: 10.15288/jsad.2008.69.611
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 30-Day Version of the Brief Young Adult Alcohol Consequences Questionnaire for Use in Longitudinal Studies

Abstract: Objective-The Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ; Kahler et al., 2005) was developed using item response modeling to provide a brief and readily interpretable measure of negative alcohol consequences over the past year among college students. The purpose of the present study was to extend evaluation of the B-YAACQ by examining its psychometric properties when administered to college students cited for a university alcohol violation using a past 30-day timeframe of assessment.Method-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(135 citation statements)
references
References 12 publications
4
127
2
2
Order By: Relevance
“…To address this concern, age was covaried for all analyses which used this measure. Studies have found correlations between the B-YAACQ and other non-age-specific alcohol use consequences measures (i.e., Alcohol Use Disorders Identification Test, Rutgers Alcohol Problem Index) to range from .70 to .79 (Kahler et al, 2008;Pearson et al, 2012;Verster et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To address this concern, age was covaried for all analyses which used this measure. Studies have found correlations between the B-YAACQ and other non-age-specific alcohol use consequences measures (i.e., Alcohol Use Disorders Identification Test, Rutgers Alcohol Problem Index) to range from .70 to .79 (Kahler et al, 2008;Pearson et al, 2012;Verster et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-related consequences were assessed using the 24-item Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ; Kahler et al, 2005), a reliable and sensitive assessment of changes in alcoholrelated consequences over time (Kahler et al, 2008). Dichotomous (yes/no) items were summed for a total number of consequences experienced in the past month.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to indicate whether they had experienced any of 24 alcohol-related consequences on each drinking day, using items from the Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ; Kahler et al, 2005). The 24-item B-YAACQ uses a subset of items from the original 48-item YAACQ (Read et al, 2006) that are minimally redundant and that most closely follow a unidimensional model (i.e., representing a continuum from less to more severe alcohol consequences in college students) and demonstrate strong psychometric properties (Kahler et al, 2005(Kahler et al, , 2008. Example items include missed work or classes at school because of drinking, passed out from drinking, and had problems with boyfriend/girlfriend/spouse/parents because of drinking.…”
Section: Methodsmentioning
confidence: 99%